First Molecular Characterization of Siphoviridae-Like Bacteriophages Infecting Staphylococcus hyicus in a Case of Exudative Epidermitis - Tetens, Julia; Sprotte, Sabrina; Thimm, Georg; Wagner, Natalia; Brinks, Erik; Neve, Horst; Hölzel, Christina Susanne; Franz, Charles M. A. P. (Frontiers in Microbiology, 2021)
Exudative epidermitis (EE), also known as greasy pig disease, is one of the most frequent skin diseases affecting piglets. Zoonotic infections in human occur. EE is primarily caused by virulent strains of Staphylococcus (S.) hyicus. Generally, antibiotic treatment of this pathogen is prone to decreasing success, due to the incremental development of multiple resistances of bacteria against antibiotics. Once approved, bacteriophages might offer interesting alternatives for environmental sanitation or individualized treatment, subject to the absence of virulence and antimicrobial resistance genes. However, genetic characterization of bacteriophages for S. hyicus has, so far, been missing. Therefore, we investigated a piglet raising farm with a stock problem due to EE. We isolated eleven phages from the environment and wash water of piglets diagnosed with the causative agent of EE, i.e., S. hyicus. The phages were morphologically characterized by electron microscopy, where they appeared Siphoviridae-like. The genomes of two phages were sequenced on a MiSeq instrument (Illumina), resulting in the identification of a new virulent phage, PITT-1 (PMBT8), and a temperate phage, PITT-5 (PMBT9). Sequencing of three host bacteria (S. hyicus) from one single farm revealed the presence of two different strains with genes coding for two different exfoliative toxin genes, i.e. exhA (2 strains) and exhC (1 strain). The exhC-positive S. hyicus strain was only weakly lysed by most lytic phages. The occurrence of different virulent S. hyicus strains in the same outbreak limits the prospects for successful phage treatment and argues for the simultaneous use of multiple and different phages attacking the same host.